Electrogenicity of Na(+)-coupled bile acid transporters. - Weinman, S. A. (Yale Journal of Biology and Medicine, 1997)
The Na(+)-bile acid cotransporters NTCP and ASBT are largely responsible for the Na(+)-dependent bile acid uptake in hepatocytes and intestinal epithelial cells, respectively. This review discusses the experimental methods available for demonstrating electrogenicity and examines the accumulating evidence that coupled transport by each of these bile acid transporters is electrogenic. The evidence includes measurements of transport-associated currents by patch clamp electrophysiological techniques, as well as direct measurement of fluorescent bile acid transport rates in whole cell patch clamped, voltage clamped cells. The results support a Na+:bile acid coupling stoichiometry of 2:1.